The Manajemen Pembinaan Tim Sepak Bola Salatiga Usia 17 Tahun 2019 (Universitas Negeri Semarang, 2021)
Purpose of the study was to determine the organizational management and coaching carried out by the Salatiga football team U 17 in 2019. The research method applied was qualitative. The methods were observation, interviews, and documentation. The subjects of this study were managers, coaches and players. The data analysis technique applied was data triangulation technique. The data analysis were done by data collection, data reduction, data presentation, and data conclusion. The results of the study indicated that 1) the organization was running well; 2) the implementation was going well; 3) the supervision has not been going well, this was proven by the absence of a clear working system in every working evaluation; 4) coaching that was carried out was running well; 5) the facilities and infrastructure used were adequate but incomplete; 6) the achievements gained were quite good. Therefore, from the results of the study, it can be concluded that the coaching management of the Salatiga football team U 17 in 2019 has been going well, but there were additions in terms of planning and supervision which were needed better communication between each department, then improving the facilities and infrastructure to support training.